HIV sero-conversion during late pregnancy - when to retest - Emma Kalk; Amy Slogrove; David P Speert; Julie A Bettinger; Mark F Cotton; Monika Esser (AOSIS, 2013)
The South African National Prevention of Mother-to-Child Transmission of HIV programme has resulted in significant reductions in vertical transmission, but new infant HIV infections continue to occur. We present two cases of HIV seroconversion during late pregnancy, demonstrating the limitations of the current programme. These could be mitigated by expanding the programme to include maternal testing at delivery and at immunisation clinic visits as we pursue the elimination of mother-to-child transmission.